2020
DOI: 10.1038/s41467-020-17363-6
|View full text |Cite
|
Sign up to set email alerts
|

An FGF15/19-TFEB regulatory loop controls hepatic cholesterol and bile acid homeostasis

Abstract: Bile acid synthesis plays a key role in regulating whole body cholesterol homeostasis. Transcriptional factor EB (TFEB) is a nutrient and stress-sensing transcriptional factor that promotes lysosomal biogenesis. Here we report a role of TFEB in regulating hepatic bile acid synthesis. We show that TFEB induces cholesterol 7α-hydroxylase (CYP7A1) in human hepatocytes and mouse livers and prevents hepatic cholesterol accumulation and hypercholesterolemia in Western diet-fed mice. Furthermore, we find that cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 64 publications
7
58
0
Order By: Relevance
“…Extracellular signal-regulated kinase (ERK) phosphorylates the site of TFEB S142 and makes it relocated in the cytoplasm ( Yonekawa et al, 2015 ; Li et al, 2019 ). Phosphorylation of TFEB S142 by mTOR/ERK inhibits nuclear translocation of TFEB in hepatocytes and thus promotes hepatic cholesterol accumulation ( Wang et al, 2020a ). Whereas AKT (protein kinase B) negatively controls TFEB through phosphorylation at S467 ( Palmieri et al, 2017 ).…”
Section: The Specific Mechanism For Tfeb Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular signal-regulated kinase (ERK) phosphorylates the site of TFEB S142 and makes it relocated in the cytoplasm ( Yonekawa et al, 2015 ; Li et al, 2019 ). Phosphorylation of TFEB S142 by mTOR/ERK inhibits nuclear translocation of TFEB in hepatocytes and thus promotes hepatic cholesterol accumulation ( Wang et al, 2020a ). Whereas AKT (protein kinase B) negatively controls TFEB through phosphorylation at S467 ( Palmieri et al, 2017 ).…”
Section: The Specific Mechanism For Tfeb Activationmentioning
confidence: 99%
“…This mechanism may contribute to the prevention of hypercholesterolemia and metabolic disorders. Bile acid-induced fibroblast growth factor 19 mediates feedback inhibition of TFEB activity and nuclear translocation via activating the mTOR/ERK pathway and phosphorylating TFEB ( Wang et al, 2020a ).…”
Section: The Function and Molecular Mechanism Of Tfeb Regulating Lipimentioning
confidence: 99%
“…Conversely, TFEB reduces the expression of enzymes involved in some lipid biosynthetic pathways [69]. However, in mice fed with western diet, TFEB overexpression has been reported to upregulate enzymes involved in cholesterol and bile acid synthesis [70]. In adipose tissue, TFEB expression stimulated by glucose and insulin is necessary to sustain adipocyte differentiation by a mechanisms mediated by Ppar2 [71], which promotes lipogenesis [72].…”
Section: Metabolismmentioning
confidence: 99%
“…Studies have revealed that primary BAs synthesized in the liver can be transformed into secondary BAs by the metabolic activities of enteric anaerobic bacteria [ 22 ]. At the terminal ileum, the majority of BAs are reabsorbed by multiple protein complexes, such as ileal bile acid-binding protein (Ibabp) and apical sodium-dependent bile acid transporter (ASBT) into enterocytes [ 23 ]. This is followed by their secretion into the portal circulation via the basolateral BA transporters organic solute transporter subunit- α (OST- α ), OST- β , and multidrug resistance-associated protein 2 (MRP2).…”
Section: Introductionmentioning
confidence: 99%
“…The underlined procedures consist of the whole enterohepatic circulation of BA [ 18 , 24 ]. BA de novo synthesis in the liver depends on the regulatory factors such as FXR and its downstream targets in the ileum and liver [ 23 , 25 ]. The whole circulation of BAs effectively emulsifies and drives the fat-soluble vitamins or lipid absorption in the intestine [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%